(untitled) (Theatrum historiae, 2012)
The study deals with the construction of the hunting Chateau of Ohrada near Hluboká nad Vltavou. The opening part of the paper presents a critical evaluation of previous Bayer investigations. The author builds upon the texts by Milena Bartlová and considers the possible reasons for the contrary evaluations of the builder by F. Mareš, H. G. Franz and V. Naňková to stem from their implicitly nationalistic standpoints. The main part of the paper analyses the correspondence from the period of the building of the chateau in 1708-1713. Following the methodological ideas by J. Kroupa, P. Fidler and P. Vlček, the author attempts to reconstruct the builder’s interventions with the process of planning and building the Chateau of Ohrada. The author holds that the hunting chateau is not the result of an individual’s creative genius. He perceives the result as an intersection of a number of mutually influential factors dominated by the investor’s interest. At the same time, Jan Ivanega summarises the research of the contemporary inventories which enabled reconstructing the use of the individual areas and subsequently looks out over the Baroque landscape surrounding the chateau. The study also contains a transcript of a letter with the builder’s inquiries and the investor’s replies.